Perancangan Sistem Informasi Pelacakan Alumni Pada Program Studi Sistem Informasi Berbasis WEB - Yudie Irawan; Syafiul Muzid; Dwi Puspitasari (Universitas Muria Kudus, 2014)
The research discusses the development of alumni tracking system using a web-based information technology. Development of the sistem using Waterfall model. At the planning stage researchers collected data from studies program manager of alumni, alumni data from several faculty and administrative data collection directly from the alumni. Those data used by researcher to analyze the proposed alternative system requirement at the analysis phase. At the design stage researchers to develop alternative systems chosen to make the system design and database design. Researchers using the Unified Modeling Language (UML) in the presentation of system design and database design. The final stage is the implementation of a design to a form web based application. Researchers using Hypertext Preprocessor (PHP) in building the system and the MySQL database in the development of physical database. The system is based website